Identification of alcoholic compounds in fermented glutinous rice (tapai) - Abdul Hamid, N. H.; Mat Hashim, Dzulkifly; Mustafa, Shuhaimi; Che Man, Yaakob (Halal Products Research Institute, Universiti Putra Malaysia, 2009)
Fermented glutinous rice (tapai) is a popular dessert amongst Malaysian consumers. However,consumption of tapai had rise the Halal issue to the Muslim community since its alcohol content is similar to beer which is 5 %. Furthermore, the aim of this study is to provide information about alcoholic compounds in tapai other than ethanol. The identification of the alcoholic compounds was performed using headspace coupled to gas chromatography flame ionization detector (HSGC-FID). The tapai was fermented in the laboratory for 3 days at 300C using inoculum obtained from Malaysian Agricultural Research and Development Institute (MARDI). It was found that after 3 days, the alcohols detected were short chain and long chain alcohol. Short chain alcohol was ethanol, and the long chain alcohols were 1-propanol, 2-methyl-1-propanol and 3-methylbutanol.